2003
DOI: 10.1113/jphysiol.2003.046250
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Rat Kv1.2 Channels Suppress Synaptic Terminal Hyperexcitability Following Action Potential Invasion

Abstract: Voltage‐gated K+ channels activating close to resting membrane potentials are widely expressed and differentially located in axons, presynaptic terminals and cell bodies. There is extensive evidence for localisation of Kv1 subunits at many central synaptic terminals but few clues to their presynaptic function. We have used the calyx of Held to investigate the role of presynaptic Kv1 channels in the rat by selectively blocking Kv1.1 and Kv1.2 containing channels with dendrotoxin‐K (DTX‐K) and tityustoxin‐Kα (Ts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
154
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(177 citation statements)
references
References 29 publications
22
154
1
Order By: Relevance
“…Kv, K 1 channel; LVA, low voltage-activated; HVA, high voltage-activated; VCN, ventral cochlear nucleus; DCN, dorsal cochlear nucleus. Dodson et al 2003;Pál et al 2004)], which is also indicated in Tables 2-4. Table 2 summarizes the results of experiments aimed at the detection of the dendrotoxin-sensitive LVA channel subunits.…”
Section: Kv Subunit Expression Pattern Of the Cn Neuronsmentioning
confidence: 93%
See 1 more Smart Citation
“…Kv, K 1 channel; LVA, low voltage-activated; HVA, high voltage-activated; VCN, ventral cochlear nucleus; DCN, dorsal cochlear nucleus. Dodson et al 2003;Pál et al 2004)], which is also indicated in Tables 2-4. Table 2 summarizes the results of experiments aimed at the detection of the dendrotoxin-sensitive LVA channel subunits.…”
Section: Kv Subunit Expression Pattern Of the Cn Neuronsmentioning
confidence: 93%
“…Table 2 summarizes the results of experiments aimed at the detection of the dendrotoxin-sensitive LVA channel subunits. As seen, the expression of the Kv1.1 subunit has been well documented in several species and in various cell types, especially in the VCN (Sequier et al 1990;Wang et al 1994;Grigg et al 2000;Bal and Oertel 2001;Dodson et al 2003;Rosenberger et al 2003;Caminos et al 2005;Jung et al 2005;Pál et al 2005;Bortone et al 2006). In the DCN, however, the situation is somewhat less clear; although the general presence of Kv1.1 protein has been noted (Sequier et al 1990;Wang et al 1994), cell-specific labeling was reported in the bat only (Rosenberger et al 2003).…”
Section: Kv Subunit Expression Pattern Of the Cn Neuronsmentioning
confidence: 99%
“…The M-type current (mediated by K v 7.2-7.5) is proven as a target by the effect of retigabine and other channel openers in amygdala-kindled seizures. Presynaptic Atype K ϩ currents are also particularly significant, 427 because genetic defects in K v 1.1 in mice and humans are associated with partial or limbic seizures. 35,114 -116 The channels responsible for the A-type current would therefore appear to be promising targets.…”
Section: Molecular Targets For the Treatment Of Limbic Seizuresmentioning
confidence: 99%
“…Several subtypes of voltage-gated potassium channels have been identified in myelinated and unmyelinated axons. K v 1.1, K v 1.2, K v 1.4, K v 3.1 and K v 3.4 have been identified in mammalian axons [6][7][8][9][10][11][12][13][14] . In addition, large-conductance calcium-dependent potassium channels (BK, also called Maxi-K or Slo1 channels) are present in axons and presynaptic terminals [15][16][17][18][19] .…”
Section: Functional Computation In the Axonmentioning
confidence: 99%